The Role of Non-Classroom Activates in Developing University Student’s Personality: The Importance and Requirements - Farouk Saleh, Emad (Al-Adab Journal, 2020)
The present paper attempts to highlight the importance of Non-classroom activities which carried out through the plans of deanships and departments of student affairs and youth welfare in universities, colleges and higher and intermediate institutes; Where Non-classroom activities play no less important role than the academic role practiced with the student systemTherefore, it includes a set of important axes that we will try to address in order to ensure the linking elements of the components of the educational process to each other, which leads to clarify the role played by these programs, Non-classroom activities in the preparation and refine and the formation of mature personality of the university student. This paper also deals with the role of supervisors of student groups in increasing the construction and preventive value of Non-classroom activities which has been implemented by of student groups members.Therefore, the knowledge and skills that must be available in the student groups supervisors should be addressed. In the end, we are expected to make some recommendations that can help all parties involved in organizing these Non-classroom programs and activities to ensure their practice and development to take advantage of their positive effects on of students' personality developing and its maturity.